Clinical assessment and screening of stroke patients with aphasia: a best practice implementation project. Issue 2 (11th June 2022) - Wang, Run; Wei, Wei; Zhou, Jungui; Yu, Mei; Zhang, Xiaomei; Luo, Yansi; Yang, Lixiao; Ye, Xiaoling; Wu, Yanni; Zhou, Chunlan
ABSTRACT: Introduction and aims: As a critical form of stroke damage, aphasia negatively impacts stroke patients' return to society. Speech and language intervention has been found to assist in optimizing poststroke aphasia patient outcomes; consequently, early identification and diagnosis are vital for poststroke aphasia to ensure that patients receive the rehabilitation they require. This project aimed to promote evidence-based practice (EBP) in the assessment and screening of stroke patients with aphasia and to improve the clinical outcomes of patients who suffer from poststroke aphasia in a large tertiary hospital. Methods: The current evidence implementation project was conducted in the neurology and rehabilitation departments of a tertiary hospital in China. Six audit criteria were developed for the baseline and follow-up audits. The project used the JBI PACES software, as well as JBI's Getting Research into Practice audit and feedback tool, to foster evidence-based healthcare in practice. Results: Although the performance of all evidence-based criteria during the baseline audit was poor, barriers were identified through baseline, and the project team carried out and implemented developed strategies following Getting Research into Practice resources. All the criteria improved from baseline after the follow-up cycle, with four out of six criteria achieving a compliance rate of 100%, and two evidence-based criteria recorded at 73 and 80% compliance, respectively. Conclusion: The current project successfully increased EBP for the assessment and screening of stroke patients with aphasia. Further studies are needed to ensure the project's long-term sustainability.